Pendidikan Keluarga dalam Pemikiran Sahal Mahfudh - M. Sofyan al-Nashr (BUANA GENDER : Jurnal Studi Gender dan Anak, 2016)
This paper aims to reveal Sahal Mahfudh’s thought on family education. This study used an interpretative method, that is a method that uses the work of a public figure then being examined in order to grasp the meaning of the distinctively embedded notion. According to Kiai Sahal, the hope to embody benefit for other people can be achieved through the benefit of the family as the smallest unit of the society. The Maslahah family is the family whose members are able to understand their rights and obligations as equivalent as their understanding of the rights and obligations of others. A good family education has a great potential to produce a qualified generation that will provide a positive impact on the society. Family education initiated by Kiai Sahal aims at providing ‘maslahah’ to the society. One of the family education output is a child who has a noble character and manner, a ‘shalih’ and ‘akram’ individual, also a productive human.Tulisan ini bertujuan untuk mengungkap pemikiran Sahal Mahfudh tentang pendidikan keluarga. Untuk menguak pemikiran Kiai Sahal digunakan metode interpretatif, yakni metode yang menggunakan karya tokoh kemudian diselami untuk menangkap arti dari nuansa yang dimaksudkan tokoh secara khas. Menurut Kiai Sahal, cita-cita mewujudkan kemaslahatan umat dapat tercapai melalui maslahatnya unit terkecil dari masyarakat, yaitu keluarga. Keluarga maslahah yaitu keluarga yang setiap anggota keluarganya mampu memahami hak dan kewajibannya setara dengan pemahamannya atas hak dan kewajiban orang lain. Pendidikan keluarga yang baik berpotensi besar menghasilkan generasi berkualitas yang dapat memberikan dampak positif bagi masyarakat. Pendidikan keluarga yang digagas Kiai Sahal ditujukan untuk memberikan maslahah kepada masyarakat umum. Salah satu output dari pendidikan keluarga ialah anak dengan watak dan perilaku mulia, insan shalih dan akram, serta manusia yang produktif.